Assessment of Medical Rehabilitation Patients on Service Convenience (Indian Journal of Public Health Research & Development, 2020)
Background: In the last 3 years outpatient installations have not been able to reach the specified patientsatisfaction standard. The existence of a tiered BPJS system made the visit of the Medical RehabilitationPoly to be poly with the most number of visits among other poly. After conducting the data survey at thebeginning it was known that the patient’s satisfaction was still low at the Medical Rehabilitation Poly with70% of patients stating that they were not satisfied with the facilities and services available.Objective: The purpose of this study was to analyze the respondents’ assessment of service convenience atthe Medical Rehabilitation Center.Method: This study was analytic observational with a cross sectional approach. The population in this studywere all patients at the Medical Rehabilitation Poly in 2017. The samples used were 333 respondents. Thestudy was conducted using a questionnaire by asking questions directly to the respondents.Result: Based on service convenience dimensions, respondents rated decision convenience as good, verygood access convenience, good transaction convenience, and good benefit convenience. There is only onevariable that is poorly assessed, namely service waiting time in transaction convenience.Conclusion: The conclusion of this study is that respondents considered that service convenience in theMedical Rehabilitation Poly of Rumah Sakit Islam A. Yani Surabaya was good.
Keywords: Assessment, Satisfaction, Service Convenience